Schwannoma with an Uncommon Upper Lip Location and Literature Review. (26th February 2013) - Bayindir, Tuba; Kalcioglu, M. Tayyar; Cicek, Mehmet T.; Karadag, Nese; Karaman, Abdurrahman
Abstract : Schwannomas are usually single, encapsulated, and benign tumors of the nerve sheath that arise from the perineural Schwann cells. Schwannomas are mostly seen in the fourth decade. Despite its location in the head and neck region is 25–45%, lip location of schwannoma are very rare. We present a case of a upper lip schwannoma in the pediatric age and review the literature.